Syntheses and single crystal X-ray diffraction analysis of five isostructural 2D MOCCs - Singh, Sandeep K.; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Polyhedron, 2018)
Five two-dimensional metal-organic coordination compounds (MOCCs) have been solvothermally synthesized by the combination of 2-aminonicotinic acid (ANA) and transition metal ions, viz. Co(II), Ni (II), Cu(Il), Zn(II) and Cd(II), in water-ethanol mixed solvent. They are formulated as [CoC6H5N2O2)(2)], (Co-ANA); [Ni(C6H5N2O2)(2)], (Ni-ANA) [Cu(C6H5N2O2)(2)], (Cu-ANA), [Zn(C6H5N2O2)(2)], (Zn-ANA) and [Cd(C6H5N2O2)(2)], (Cd-ANA). Single crystal X-ray diffraction studies for the complexes Co-ANA, Ni-ANA and Cd-ANA have also been carried out. These three complexes crystallize in the tetragonal crystal system with the space group P4(1)2(1)2. The metal ions in all these complexes have an octahedral coordination environment. The six coordinations are satisfied by two pyridine N-atoms from two different ANA ligands and four oxygen atoms from two chelating carboxylate groups of another two ANA ligands. The topological motif of the coordination network is defined as 2-periodic net or square lattice (sql). These complexes were further characterized by elemental, FT-IR spectral, thermal and powder X-ray diffraction analyses. (C) 2018 Elsevier Ltd. All rights reserved.